Characterization of BaZrO3 nanocolumns in Zr-added (Gd, Y)Ba2Cu3Ox superconductor tape by anomalous small-angle x-ray scattering. (9th April 2019) - Oba, Yojiro; Sasaki, Hirokazu; Yamazaki, Satoshi; Nakasaki, Ryusuke; Ohnuma, Masato
Abstract: BaZrO3 nanocolumns in (Gd, Y)Ba2 Cu3 O x superconductor tapes have been characterized by anomalous small-angle x-ray scattering (ASAXS). As Zr is distributed only in the nanocolumns, the scattering from the nanocolumns can be separated using ASAXS measurements at the Zr K absorption edge. The ASAXS results showed that the distance between the nanocolumns decreases from 37 to 28 nm with increasing the content of Zr from 15 to 25 mol%. The average diameter of the nanocolumns increases up to Zr content of 20 mol%, while the average diameter of the 25 mol% Zr sample is similar to that of the 20 mol% Zr sample. These results confirm that ASAXS measurements are useful for the characterization of BaZrO3 nanocolumns.